Clinical and radiographic evaluation of zinc oxide with aloe vera as an obturating material in pulpectomy: An in vivo study - Abhishek Khairwa; Manohar Bhat; Rajesh Sharma; V Satish; Prabhadevi Maganur; Anil Kumar Goyal (Wolters Kluwer Medknow Publications, 2014)
Background: Pulp therapy for pulpally involved primary teeth continues to be a challenge to clinicians. One of the major areas of continued research is in the area of finding obturating materials to suit the specific properties of these teeth. Zinc oxide eugenol is used frequently in pulpectomy for the obturation of the primary teeth. Aims: To evaluate clinically and radiographically a mixture of zinc oxide eugenol and aloe vera as an obturating material. Materials and Methods: A total of 50 children, aged between 4 and 9 years, who were screened for unilateral or bilateral carious deciduous molars were studied. Out of these, 15 children were randomly selected for endodontic treatment. Obturation was done with a mixture of zinc oxide powder and aloe vera gel. Clinical and radiographic evaluation was done after 7 days, 1 month, 3 months, 6 months, and 9 months. The data were statistically analyzed. Results and Conclusion: Endodontic treatment using a mixture of zinc oxide powder and aloe vera gel in primary teeth has shown good clinical and radiographic success. A detailed observational study with longer follow-up will highlight the benefits of aloe vera in primary teeth as an obturating medium.